Taxonomy of Acinetobacter: the usefulness of beta-D-xyloside xylohydrolase for strain differentiation. Issue 9 (September 1977) - Hansen, W; Schoutens, E; Yourassowsky, E
Abstract : One hundred and twenty-two clinical isolates of Acinetobacter were studied for the presence of beta-galactosidase and of beta-xylosidase, for biochemical characteristics, and for genetic interspecies transformation tests. All strains lacked beta-galactosidase; in contrast, beta-xylosidase was always present in the oxidative strains. This test proved to be of value for separating strains able to form acid from carbohydrates (A. anitratum and A. haemolyticus spp haemolyticus) from the non-oxidative strains (A. lwoffi and A. haemolyticus spp alcaligenes). However, the genetic relationship of all strains tested warrants further study before Acinetobacters are grouped into clearly defined species.